(untitled) (Journal of Oriental Studies, 2018)
The article comparative analysis of translation of proper names in the book by Su Beihai “The History of Kazakh Culture”, which was translated into Kazakh in Kazakhstan and China. The use of different types of translations was analyzed, such as mixed translation, semantic translation and loan translation that are used in the translation process; solutions for the full preservation of the original contents were investigated. The performed comparison helped to identify the processes of formation of the difference in the use of terms accepted by Kazakhs from Kazakhstan and China. The author gives a personal opinion that such a phenomenon is associated with different principles of transcription, which are used for proper names and terms in Chinese. It is concluded that this problem can be solved by using the Latin alphabet.